Measuring influenza hemagglutinin (HA) stem-specific antibody-dependent cellular cytotoxicity (ADCC) in human sera using novel stabilized stem nanoparticle probes. Issue 4 (22nd January 2020) - Smatti, Maria K.; Nasrallah, Gheyath K.; Al Thani, Asmaa A.; Yassine, Hadi M.
Abstract: Background: Generating vaccine that confers a complete protection is a major goal in designing a universal influenza vaccine. Currently, there is a considerable interest in the broadly neutralizing antibodies (bnAb) targeting the conserved HA stem region. These antibodies have been shown to activate cellular immune responses, such as ADCC, in addition to their neutralization activity. We had previously demonstrated that immunization with H1-based stabilized stem (SS) nanoparticles (np) protects against heterosubtypic lethal H5N1 challenge, despite the absence of detectable neutralizing activity. Utilizing these novel SS probes to develop an ADCC assay would help in understanding the mechanism of action of stem-specific antibodies, as well as evaluating future influenza vaccines. Objectives: To develop a new protocol to assess the ADCC activity mediated by stem-directed antibodies in human sera using novel SS np probes. Study design: Human sera samples were screened for binding and ADCC activities to different influenza group 1 SS probes (H1, H2, and H5) using trimeric SS or multivalent SS-np (n = 8 trimers) formats. Results: Initial screening revealed 63% (57/90) seroprevalence of anti-HA (H1) stem-epitope antibodies, as determined by the differential binding to HA SS and its corresponding epitope-mutant (Ile45Arg/Thr49Arg) probe. Using equimolar amounts, the multivalent presentation of HA SS on np induced significantly higher ADCC activity compared to the monovalent (trimer) SS probes (2–6 fold increase). Further, ADCC activity was similarly reported against different group 1 influenza subtypes: H1, H2, and H5. Importantly, ADCC was mediated mainly by antibodies targeting the bnAb-epitope on the HA stem. Conclusion: We report on an assay to measure stem-specific ADCC activity using SS np probes. Our results indicate high prevalence of HA-stem antibodies with cross-reactive ADCC activity. Such assay could be utilized in the assessment of next generation influenza vaccines.